ROSUS 2025 - Računalniška obdelava slik in njena uporaba v Sloveniji 2025: Zbornik 19. strokovne konference - Nikl Hutinski, Emanuel; Lajić, Romanela; Peer, Peter; Emeršič, Žiga; Šter, Rok Marko; Podobnik, Gašper; Vrtovec, Tomaž; Emeršič, Žiga; Hrastnik, Gregor; Meh Peer, Nataša; Peter Peer, Peter Peer; Šavc, Martin; et al. (2025)
ROSUS 2025 - Computer image processing and its application in Slovenia 2025: Proceedings of the 19th Professional Conference. ROSUS 2025 – Computer image processing and its application in Slovenia 2025 is a professional conference that, since 2006, has been organised every year by the Institute of Computer Science of the Faculty of Electrical Engineering and Computer Science, University of Maribor. The conference connects researchers in the fields of Image Processing and Machine Vision with users of this knowledge, whereby users are coming from diverse industrial environments, such as Biomedicine, Sport, Entertainment, and related fields. The proceedings of ROSUS 2025 combine scientific articles by dozens of authors, including two invited lectures and several demonstration articles. Contributions represent the latest achievements of Slovenian experts in the fields of Image Processing and Vision, and also highlight trends and novelties in these areas. Great emphasis is on promotion of the economic usefulness of Image Processing and Vision applications in the Slovenian region. Namely, such software, due to high precision, robustness, and exceptional speed in information processing, provides new opportunities for penetration on the high technologies market.
Keywords: evolutionary algorithm; deep networks; image classification; generating deep networks; optimization